SPORT NUTRITION - Jeukendrup, Asker E.; Gleeson, Michael (Human Kinetics, 2025)
"This book provides the scientific underpinnings of sport nutrition guidelines and advice at a level that is appropriate for students, and it is also a valuable resource for qualified sport nutrition practitioners and coaches"